Study of mechanical behavior of BNNT-reinforced aluminum composites using molecular dynamics simulations. (15th June 2018) - Cong, Ziyu; Lee, Seungjun
Abstract: Fabrication of metallic matrix boron nitride nanotubes (BNNT) composites have remained challenging due to their high reactivity of metals at elevated processing temperatures. Recently, however, the successful fabrication of BNNT-metal composites has been reported using a plasma technique. Since carbon nanotubes (CNT), which are a structural analogy of BNNTs, easily react with aluminum to form aluminum carbides at the interface, serving as mechanically weak points, BNNTs can be a good alternative for the reinforcing component of metal-matrix composites (MMC). In this study, we conducted several molecular dynamics (MD) simulations to investigate the mechanical behaviors of BNNT-Al composites under tensile loading. The simulations provided quantitative information on the mechanical properties of the BNNT composite, revealing the effect of various BNNT diameters and volume fractions. The contributions of the BNNT and Al component to the total improvement of mechanical properties were quantified through a component analysis. The analysis revealed that the effect of the volume fraction of BNNTs is more significant than that of the size. In addition, the quantified relation between the volume fraction of BNNTs and the enhancement in elasticity can be effectively used for the engineering design of BNNT-Al MMCs.